EQUALIZATION OF BROADCAST LOUDNESS USING FEED-FORWARD LOUDNESS CONTROL AND ADAPTIVE PARAMETER CONFIGURATION (FUDMA JOURNAL OF SCIENCES, 2023)
Loudness is a subjective measure of how piercing an audio signal is perceived. Due to commercial pressures loudness has been exploited in broadcasts to attract and reach viewers and listeners. Sudden changes in loudness between television channels and programs are significant causes of nuisance for the consumers.  With the transition from analogue to digital TV, loudness related issues are on the rise hence, the need for objective and accurate techniques for digital broadcast. The measurement of perceived loudness is difficult yet an important task. Many research efforts have been introduced for objective measurement and equalization of the loudness of audio channel or program in order to facilitate program delivery. In this paper, broadcast contents were examined to discover where loudness occurs in a program and how to achieve equal average loudness between broadcast programs. A modified scheme was developed based on a standard set by ITU- Radio and European Broadcasting Union by incorporating a feed forward loudness control (FLC) mechanism and an adaptive parameter configuration (APC) scheme for the purpose of addressing loudness in long and short form contents.
Keywords: Loudness, Audio Signal, Long Form Content, Short Form Content, Audio/Loudness Normalization, Program Transition